Prediction value of cystatin C for postoperative acute kidney injury of acute type A aortic dissection - Li, Shouming; Zhao, Xin; Wang, Zhenhua; Song, Han; Liu, Yongmin (Journal of Medical Biochemistry, 2025)
ObjectiveThe research aimed to provide an initial prediction of postoperative acute kidney injury in patients with acute type A aortic dissection undergoing total aortic arch replacement combined with frozen elephant trunk stent implantation by investigating the association between preoperative cystatin C levels and postoperative AKI, while incorporating relevant risk factors into the analysis.MethodsThis study employed a case-control design, involving 202 patients from a single center between January 2018 and December 2019. The participants were categorized into case group (n=73) and control group (n=129).ResultsThe univariate analysis indicated preoperative history of hypertension (P=0.013), white blood cell count (P
Keywords: acute type A aortic dissection; acute kidney injury; prediction model